Global characterization of the Quercus suber ectomycorrhizal transcriptome using 454 pyrosequencing - Sebastiana, Mónica (2011)
In temperate forests, trees live in symbiosis with fungi and depend on them for their survival. Species from the Fagaceae family, including oaks, establish a symbiotic relationship in their roots with basidiomycetous fungi, called ectomycorrhizas (ECM). ECM symbiosis is essential for the life and health of trees in temperate and boreal forests where it plays a major role in nutrient cycling and in functioning of the forest ecosystem. Trees with well developed ECM root tips are more tolerant to environmental stresses, such as drought, and iotic stresses such as root pathogens. There is a general agreement that ECM fungi increase plant survival and productivity. Cork oak is well adapted to water scarcity typical of the Mediterranean summer, due to a root system that can reach several metres in depth, and to the abundance of roots at the soil surface associated with ECM. The development of ECM symbiosis is characterized by the successive development of three structural components: a mantle of fungal tissue that encloses the root, the intraradical network of hyphae (Hartig net), where plant and fungus exchange metabolites, and the extraradical mycelium, which extends into the soil and is responsible for nutrient and water uptake. All these processes are highly regulated and are accompanied by alterations on gene expression in both partners. The current project is integrated in the effort for covering the transcriptome of Quercus suber and is focused on the identification of ESTs involved in the development of ECM symbiosis in cork oak. Since only 236 ESTs from Quercus suber are currently known, the use of genomics approaches for gene discovery or functional studies is far from being achieved for this plant species.